Up-Scalable Fabrication of SnO2 with Multifunctional Interface for High Performance Perovskite Solar Modules - Tong, Guoqing; Ono, Luis K.; Liu, Yuqiang; Zhang, Hui; Bu, Tongle; Qi, Yabing (Nano-Micro Letters, 2021)
Tin dioxide (SnO2) has been demonstrated as one of the promising electron transport layers for high-efficiency perovskite solar cells (PSCs). However, scalable fabrication of SnO2 films with uniform coverage, desirable thickness and a low defect density in perovskite solar modules (PSMs) is still challenging. Here, we report preparation of high-quality large-area SnO2 films by chemical bath deposition (CBD) with the addition of KMnO4. The strong oxidizing nature of KMnO4 promotes the conversion from Sn(II) to Sn(VI), leading to reduced trap defects and a higher carrier mobility of SnO2. In addition, K ions diffuse into the perovskite film resulting in larger grain sizes, passivated grain boundaries, and reduced hysteresis of PSCs. Furthermore, Mn ion doping improves both the crystallinity and the phase stability of the perovskite film. Such a multifunctional interface engineering strategy enabled us to achieve a power conversion efficiency (PCE) of 21.70% with less hysteresis for lab-scale PSCs. Using this method, we also fabricated 5 × 5 and 10 × 10 cm2 PSMs, which showed PCEs of 15.62% and 11.80% (active area PCEs are 17.26% and 13.72%), respectively. For the encapsulated 5 × 5 cm2 PSM, we obtained a T80 operation lifetime (the lifespan during which the solar module PCE drops to 80% of its initial value) exceeding 1000 h in ambient condition. Highlights: 1 High-quality large-area SnO2 films are fabricated by chemical bath deposition with the addition of KMnO4. 2 The presence of K and Mn ions can improve both the crystallinity and the phase stability of perovskites and reduce hysteresis of devices simultaneously. 3 Perovskite solar modules (22.4 and 91.8 cm2) are demonstrated with active area efficiencies of 17.26% and 13.72%, respectively, and the 22.4 cm2 perovskite solar module exhibits a T80 operation lifetime exceeding 1000 h in ambient condition.